2020
DOI: 10.1021/acs.organomet.0c00082
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Investigation of the Nickel-Catalyzed Carbonylation of Alcohols

Abstract: The carbonylation of alcohols represents a straightforward and atom-efficient methodology for the preparation of carboxylic acids. It is desirable to perform these reactions under precious metal-free and low-pressure conditions, with regioselectivity control. In this work, we present a detailed mechanistic study of a catalytic system based on NiI2, which can carbonylate benzylic alcohols in a highly regioselective manner to the corresponding branched carboxylic acids, core motifs for nonsteroidal drugs. The co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 68 publications
(104 reference statements)
2
16
0
Order By: Relevance
“…Even though the transformation of the alcohol to the alkyl iodide species is a simple S N 1 reaction, which should favor the formation of tert -butyl iodide ( t BuI) from t BuOH, one could envision that isobutyl iodide ( i BuI) can also be formed, which would then be converted to isovaleric acid. In our previous study, we have shown that cyclohexyl carboxylic acid can be obtained in roughly the same yield both from cyclohexanol with NiI 2 and iodocyclohexane in cyclohexanol (1:9) and Ni­(cod) 2 (cod = 1,5-cyclooctadiene) . If the reaction under investigation follows the same pathway, this separation of reaction steps needs to be possible as well.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Even though the transformation of the alcohol to the alkyl iodide species is a simple S N 1 reaction, which should favor the formation of tert -butyl iodide ( t BuI) from t BuOH, one could envision that isobutyl iodide ( i BuI) can also be formed, which would then be converted to isovaleric acid. In our previous study, we have shown that cyclohexyl carboxylic acid can be obtained in roughly the same yield both from cyclohexanol with NiI 2 and iodocyclohexane in cyclohexanol (1:9) and Ni­(cod) 2 (cod = 1,5-cyclooctadiene) . If the reaction under investigation follows the same pathway, this separation of reaction steps needs to be possible as well.…”
Section: Resultsmentioning
confidence: 97%
“…The previously developed, radical-based mechanism builds on the conversion of alcohol to the corresponding alkyl iodide, which is then carbonylated with CO (see Scheme ). The investigated catalytic cycle starts from the diphosphine-dicarbonyl-nickel(0) complex 1 that is formed via the in situ reduction of NiI 2 in the presence of TBP and CO. After the initial phosphine dissociation, 1 forms an adduct with the tert -butyl halide 2- t Bu or isobutyl halide 2- i Bu (Δ G 453 = 107.3 and 110.5 kJ mol –1 , respectively). Barrierless homolytic cleavage of the C–I bond in 2- t Bu/2- i Bu leads to the formation of 3 and the corresponding t Bu or i Bu radical ( 3 + t Bu • : Δ G 453 = 94.4 kJ mol –1 ; 3 + i Bu • : Δ G 453 = 120.8 kJ mol –1 ), which can quickly recombine to form Ni­(II) complex 4- t Bu (Δ G 453 = 135.6 kJ mol –1 ) or 4- i Bu (Δ G 453 = 125.4 kJ mol –1 ), depending on the substrate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past decade, Buchwald-type phosphines have also found successful application in a limited number of Nicatalyzed cross-coupling reactions (Figure 1C). [17][18][19][20][21][22][23][24][25] One of the first reports came from our lab in 2011 with the development of a Ni-catalyzed cross-coupling of styrenyl epoxides and boronic acids, where BrettPhos was identified to be the most effective ligand in the transformation. 18 The Watson and Crudden labs have also reported the use of Buchwald-type phosphines in Nicatalyzed-cross coupling reactions of naphthylic pseudohalides.…”
Section: Introductionmentioning
confidence: 99%
“…Nickel complexes were once considered promising homogeneous carbonylation catalysts, as reflected in patents (17)(18)(19)(20)(21)(22) and the peer-reviewed literature (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). There are inherent economic advantages of an abundant and inexpensive nickel catalyst: a metric ton of nickel can cost the same as a troy ounce of rhodium.…”
mentioning
confidence: 99%